The Relationship between handwashing behaviour and the incidence of covid-19 disease prevention - Milawati, Rina; Teresa, Teresa (Science Midwifery, 2024)
Background: Pandemic diseases occur at this time, including diseases that interfere with the respiratory tract, called Covid -19, caused by a virus. The spread of disease depends on people's behavior in carrying out prevention. One way to prevent this disease is by washing your hands properly. Purpose: this study aims to determine the relationship between community behavior in carrying out good hand washing in preventing the transmission of Covid-19 disease. Methods: this study used a cross-sectional method with the chi square test technique. A sample of 40 people. Results: showed that 23 respondents had good knowledge (56.4%) and 34 respondents had good hand washing behavior (82%). Conclusion: there is a relationship between handwashing behavior and the incidence of prevention of transmission of covid -19 pValue- 0.001. Suggestions for residents to continue to practice healthy behavior habits: wash hands during the Covid-19 pandemic to stay awake from disease transmission.